Handbook of induction heating - Rudnev, Valery; Loveless, Don (Consultant); Cook, Raymond (Vice President at Inductoheat, Inc.) (CRC Press, Taylor & Francis Group, 2017)
"The second edition of the Handbook of Induction Heating reflects the number of substantial advances that have taken place over the last decade in theory, computer modeling, semi-conductor power supplies, and process technology of induction heating and induction heat treating. This edition continues to be a synthesis of information, discoveries, and technical insights that have been accumulated at Inductoheat Inc., at industry and academia"-- Provided by publisher
Keywords: Induction heating.; Furnaces -- Industrial applications.; elektronické knihy; electronic books